Answer:
[tex]y =-\frac{1}{2}(x +2)(x - 3)[/tex]
Step-by-step explanation:
Given
[tex]x_1 = -2[/tex]
[tex]x_2 = 3[/tex]
[tex](x,y) = (-1,2)[/tex] --- a point on the parabola
Required
The equation
First, calculate the equation from the zeros
[tex]y =k(x - x_1)(x - x_2)[/tex]
Substitute [tex]x_1 = -2[/tex] and [tex]x_2 = 3[/tex]
[tex]y =k(x - -2)(x - 3)[/tex]
[tex]y =k(x +2)(x - 3)[/tex]
To solve for k, we substitute [tex](x,y) = (-1,2)[/tex]
[tex]2 = k(-1+2)(-1-3)[/tex]
[tex]2 = k(1)(-4)[/tex]
[tex]2 = -4k[/tex]
Divide by -4
[tex]k=\frac{2}{-4}[/tex]
[tex]k=-\frac{1}{2}[/tex]
So, the equation is:
[tex]y =k(x +2)(x - 3)[/tex]
[tex]y =-\frac{1}{2}(x +2)(x - 3)[/tex]